Low-frequency generation by ionizing femtosecond laser pulse supplied by its second or half-harmonic - Laryushin, I.D.; Kuznetsov, L.S.; Kostin, V.A.; Silaev, A.A.; Vvedenskii, N.V. (Вопросы атомной науки и техники, 2015)
We calculate the free-electron residual current density excited in a gas by ionizing two-color femtosecond laser pulses containing an intense component centered at 800-nm and a weaker 400-nm (second-harmonic) or 1600-nm (half-harmonic) component with the use of quantum-mechanical (with the three-dimensional time-dependent Schrödinger equation solved numerically) and semiclassical approaches. The efficiency of residual current excitation by two-color pulses with additional second- and half-harmonic components is compared.